14–3‐3γ prevents centrosome duplication by inhibiting NPM1 function. (14th April 2021) - Bose, Arunabha; Modi, Kruti; Dey, Suchismita; Dalvi, Somavally; Nadkarni, Prafful; Sudarshan, Mukund; Kundu, Tapas K.; Venkatraman, Prasanna; Dalal, Sorab N.
Abstract: 14–3–3 proteins bind to ligands via phospho‐serine containing consensus motifs. However, the molecular mechanisms underlying complex formation and dissociation between 14–3–3 proteins and their ligands remain unclear. We identified two conserved acidic residues in the 14–3–3 peptide‐binding pocket (D129 and E136) that potentially regulate complex formation and dissociation. Altering these residues to alanine led to opposing effects on centrosome duplication. D129A inhibited centrosome duplication, whereas E136A stimulated centrosome amplification. These results were due to the differing abilities of these mutant proteins to form a complex with NPM1. Inhibiting complex formation between NPM1 and 14–3‐3γ led to an increase in centrosome duplication and over‐rode the ability of D129A to inhibit centrosome duplication. We identify a novel role of 14–3‐3γ in regulating centrosome licensing and a novel mechanism underlying the formation and dissociation of 14–3–3 ligand complexes dictated by conserved residues in the 14–3–3 family. Abstract : This article identifies novel roles of acidic residues in the 14–3–3 peptide‐binding groove that regulate association with phosphorylated ligands. The relevance of these residues to ligand function has been explored using centriole duplication as a model, and we demonstrate that 14–3–3 proteins inhibit centriole duplication by regulating NPM1 function.